ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI PERAWAT DI RUMAH SAKIT UMUM DAERAH TELUK KUANTAN TAHUN 2016 - Ade Dita Puteri (Universitas Pahlawan, 2017)
Based on Hospital Information System (SIRS in 2000), most 80% of nurses who work in hospitals are diploma III, bachelor (S1 nursing) 1% and S2 0.4%. While the educated SPK as much as 7%. This is not in accordance with the standards of the nursing profession as a professional nursing care. The purpose of this study is to see what factors are associated with nurse motivation of Teluk Kuantan Regional Hospital. This research type is descriptive analytic with cross sectional study design, with a sample of 108 respondents with total sampling technique .Data processing using chi square test. The result of the research shows that there is relationship between age and nurse motivation P = 0,001 <0,05 there is relationship between marital status with nurse motivation P = 0,001 <0,05 there is relation between nurse salary with nurse motivation P = 0,001 <0,05 there is relationship between Supervisor's support with nurse motivation continuing undergraduate education with P value = 0,001 <0,05. It can be concluded that there is a significant relationship between factors related to the motivation of nurses of Teluk Kuantan regional general hospital